2014
DOI: 10.1093/jxb/eru252
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of good- and bad-quality cork: application of high-throughput sequencing of phellogenic tissue

Abstract: Cork is one of the most valuable non-wood forest products and plays an important role in Mediterranean economies. The production of high-quality cork is dependent on both genome and environment, posing constraints on the industry because an ever-growing amount of bad-quality cork (BQC) development has been observed. In order to identify genes responsible for production of cork of superior quality we performed a comparative analysis using the 454 pyrosequencing approach on phellogenic tissue of good- and bad-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 99 publications
3
49
0
1
Order By: Relevance
“…Thus, the significant enrichment in abiotic stress transcripts may also be due to a greater exposure of holm oak outer bark to the environment, as was also described for potato tuber periderm (Barel and Ginzberg 2008;Soler et al 2011). Similarly, the overrepresentation in holm oak external bark of GO terms related to chromatin and translation could be linked to cell damage caused by abiotic stresses such as UV radiation and the need to maintain cellular homeostasis and ensure correct gene regulation (Teixeira et al 2014). Nevertheless, it can also be surmised that the induction of chromatin remodeling genes may be involved in the tight regulation of the phellogen activity in holm oak, which is active only during limited time periods, when the environmental conditions and the tree physiology are favorable.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, the significant enrichment in abiotic stress transcripts may also be due to a greater exposure of holm oak outer bark to the environment, as was also described for potato tuber periderm (Barel and Ginzberg 2008;Soler et al 2011). Similarly, the overrepresentation in holm oak external bark of GO terms related to chromatin and translation could be linked to cell damage caused by abiotic stresses such as UV radiation and the need to maintain cellular homeostasis and ensure correct gene regulation (Teixeira et al 2014). Nevertheless, it can also be surmised that the induction of chromatin remodeling genes may be involved in the tight regulation of the phellogen activity in holm oak, which is active only during limited time periods, when the environmental conditions and the tree physiology are favorable.…”
Section: Discussionmentioning
confidence: 77%
“…In relation to Q. suber, several normalized cDNA libraries covering different tissues (phellem included), organs and development stages have been pyrosequenced (Pereira-Leal et al 2014). Good-and bad-quality cork samples have also been pyrosequenced, showing that there is upregulation of putative stomatal/lenticular-associated genes in bad quality cork, which may be responsible for the higher number of lenticular channels present (Teixeira et al 2014). The corresponding phellogen tissue has also been sequenced and the results showed that in the phellogen of good-quality cork the synthesis of lignin and suberin is promoted, whereas in bad-quality cork the biosynthesis of flavonoids is favored (Teixeira et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Within a national initiative, a Portuguese consortium was created to study cork oak ESTs and thus develop a new genomic resource for studying Q. suber (Pereira-Leal et al 2014). This achievement has been used to better understand processes related with plant development (Rocheta et al 2014;Teixeira et al 2014) and adaptation responses to both biotic (Sebastiana et al 2014) and abiotic factors (Magalhães et al 2016). The global overview of up-and downregulated genes in cork oak roots following inoculation with the P. tinctorius resulted in a better insight of those molecular events that control ECM symbiosis (Sebastiana et al 2014).…”
Section: Advances For Mediterranean Fagaceae Ecm Studiesmentioning
confidence: 99%
“…Recently, an oak gene expression atlas was also generated for two sympatric oak species, Quercus robur (pedunculated oak) and Quercus petraea [9], which identified genes associated with vegetative bud phenology and contributed relevant information for the annotation of the pedunculated oak's genome. The gene expression studies performed in cork oak have mainly targeted the identification of genes involved in cork formation, and several candidate genes have been revealed [10].…”
Section: Introductionmentioning
confidence: 99%